Connective tissue disease-related interstitial lung disease is alleviated by tripterine through inhibition of the PI3K/Akt, apoptosis, and TNF-α signalling pathways - Zhu, Wen; Wang, Yifan; Liu, Chenxi; Wu, Yunxia; Li, Yehui; Wang, Yue (Frontiers in Pharmacology, 2022)
Background Interstitial lung disease (ILD) is a vital cause of morbidity and mortality in patients with various rheumatic diseases. Current treatment recommendations are mainly about glucocorticoids, immunosuppressants and antifibrosis drugs. But more interventions still need to be sought. Tripterine, an extract of Tripterygium wilfordii Hook.f., has been widely studied for its strong anti-inflammatory effect. However, the mechanism of its action in treating CTD-ILD remains unclear. Purpose To investigate the mechanism of Tripterine in the treatment of CTD-ILD by in vivo experiment and network pharmacology approach. Methods After searching the TCMSP, CTD, GeneCards, STITCH, and SymMap databases, the related targets of Tripterine were obtained. Then, OMIM, GeneCards, Genebank, and DrugBank were used to screen the targets of CTD-ILD. The target-signaling pathway network was constructed by Cytoscape and topological analysis was also carried out. Protein interaction was carried out by STRING online analysis platform. Then, GO and KEGG signal pathway enrichment analysis was conducted. Subsequently, the molecular docking between Tripterine and core target was verified. Finally, We conducted experimental verification in bleomycin (BLM) induced model mice. Results A total of 134 common targets and 10 core targets of Tripterine were collected, including STAT3, TNF, RELA, AKT1, MAPK1, JUN, TP53, MAPK3, NFKB1, and CASP8. Go enrichment analysis showed that Tripterine treatment of CTD-ILD mainly involved cytokine receptor binding, receptor-ligand activity, signal receptor activation, cytokine activity, protein ubiquitination, DNA transcriptase activity, and so on. KEGG pathway enrichment analysis showed that the most significant signal pathways were multiple virus infections, PI3K/AKT, TNF, and apoptosis signal pathway. Molecular docking results showed that Tripterine had good docking activity with core targets. Experimental studies also demonstrated that Tripterine can inhibit the activation of PI3K/AKT, Apoptosis, and TNF-α signaling pathways in lung tissue, and significantly improve lung pathology and collagen deposition in model mice. Conclusions This study preliminarily revealed the potential molecular biological mechanism of Tripterine interfering with CTD-ILD through multiple targets and pathways. The specific mechanism may be related to inhibiting the PI3K/AKT, apoptosis, and TNF-α signaling pathways. Tripterygium wilfordii Hook. f. and its extract can provide a choice for clinical treatment of CTD-ILD.